Isolation And Characterization Of Limonoids From Swietenia Macrophylla And Their Antioxidant And Antimicrobial Activities - Tan, Seok Keik (2009)
Swietenia macrophylla King, a tree up to 30-35 m tall, is used traditionally by local folks to cure diabetes and high-blood pressure. Swietenia macrophylla King. adalah sejenis pokok setinggi 30-35 m. Ia digunakan secara tradisional oleh masyarakat tempatan untuk mengubati penyakit kencing manis dan tekanan darah tinggi.